PROMOTING STUDENTS’ COLLABORATION SKILL THROUGH PROJECT BASED LEARNING OF ENGLISH WRITING - Farida Nova Kurniawati; Susanto Susanto; Ahmad Munir (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
Abstract This research is focused on Project Based Learning and collaboration skill of students. It is aimed to describe how Project Based Learning promotes students’ collaboration skill with others as one of four Cs skills in 21st of Century Skills. The subject of this study was five students in the ninth grade in one of state Islamic schools in Kediri. The researcher collected the data from observation and the recording video of the process of creating the project, which was wall magazine. The observation was done twice and the activities during the process of making wall magazine will be written in field note and recorded by using video recorder. This research highlights more on the process of creating the project rather than the product. Therefore, all the data will be in the form of verbal and non-verbal data. After selecting the appropriate data, the result shows that the students can reach all of indicators of collaboration skills with eleven examples as the evidences. In short, it can be concluded that Project Based Learning can promote students’ collaboration.Keywords : Project Based Learning, Collaboration Skill, Wall Magazine, Junior High School